Kajian Peran Sistem Imun Adaptif Terhadap Infeksi Virus Rna Pada Vertebrata - Gepri (CV. SINAR HOWUHOWU, 2025)
RNA virus infections pose a significant challenge to vertebrate health due to their high mutation rates and capacity for rapid evolution. This review aims to synthesize the understanding of the central role of the adaptive immune system in recognizing, controlling, and eliminating RNA virus infections. Through a narrative literature review approach, an in-depth analysis of the two main pillars of adaptive immunity—humoral and cell-mediated immunity—was conducted. The findings indicate that humoral immunity, mediated by B cells and antibodies, is crucial for neutralizing extracellular virus particles, thereby preventing viral attachment and entry into host cells. In parallel, cell-mediated immunity, driven by cytotoxic T cells (CD8+), is essential for eliminating already infected cells, while helper T cells (CD4+) act as key coordinators that regulate the entire response. A fundamental advantage of this response is the formation of immunological memory, which provides long-term protection and serves as the basis for vaccine efficacy. Nevertheless, the immune system faces a continuous challenge from viral evasion strategies, such as antigenic drift, which fuels an evolutionary arms race. A comprehensive understanding of this dynamic interaction is vital for the development of more effective next-generation vaccines and antiviral therapies.